Perfil socio-laboral de los profesionales en Administración en Salud de la Universidad de Antioquia 1999-2008 (2012)
ABSTRACT: To characterize the social and work profiles of the professionals from Universidad de Antioquia (University of Antioquia) who hold a degree in Health Administration. Methodology: A cross-sectional study based on primary data obtained by surveying 356 graduate professionals between 1999 and 2008. Descriptive and inferential statistical analysis techniques were applied. Depending on the nature of the variables, absolute values, ratios, and summary measures of central tendency were reported. Results: It was a group of young professionals with an average age of 32.5 years. They were mainly women with professional work experience after graduation. They were employed at the time of the survey, but 12.1% of them reported being unemployed. The main sector of the economy where they work is services, followed by construction. Their most common position is that of administrator, followed by operational positions. In most cases, their income doesn´t exceed 4 legal minimum wages. Discussion: some findings are consistent with previous studies conducted in 2001 and 2004. Other variables contrast with these studies and with other national references. We conclude that the conditions of job insecurity are not inherent to the profession itself but to the labor market characteristics of the current capitalist world.